The Notion of Secrecy A Balanced Approach in the Light of the Trade Secrets Directive - Trallero Ocaña, Teresa (Munich Intellectual Property Law Center - MIPLC Studies, 2021)
In the digital age, information has become an increasingly valuable, but at the same time vulnerable commodity. The strategic role that trade secrets play in the economy of the Single Market and the scattered legal framework across EU jurisdictions prompted the EU Commission to harmonise this field of law and to adopt the Trade Secrets Directive. This thesis analyses the conditions under which information loses its secret nature, enters the public domain and is then free for competitors to use, taking into account the legal framework created by the Trade Secrets Directive.